2014
DOI: 10.15283/ijsc.2014.7.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Stem Cell Therapies for Patients with Stroke: a Systematic Review and Single Arm Meta-Analysis

Abstract: Background and Objectives:Stem cell-based therapy is a potential new approach in the treatment of stroke. However, the efficacy and safety of these treatments are not yet fully understood. Therefore, we performed a meta-analysis of available single-arm studies using stem cell-based therapy in patients with stroke.Methods:We searched MEDLINE, EMBASE, and the Cochrane database for studies of stem cell therapy in patients with stroke from its inception through July 2014. The articles included in the search were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 29 publications
2
52
0
1
Order By: Relevance
“…It has been suggested that MSC presence promotes intra-renal accumulation of protective M2 macrophages, with increased production of the anti-inflamatory IL-10 and decrease of IL-6 and TNF-α [79]. In humans, stem-cell based therapy has been tried for stroke, with apparently good results, however different recent meta-analysis report that further investigation is needed to test clinical efficacy and safety [80,81].…”
Section: Antioxidant Treatmentmentioning
confidence: 99%
“…It has been suggested that MSC presence promotes intra-renal accumulation of protective M2 macrophages, with increased production of the anti-inflamatory IL-10 and decrease of IL-6 and TNF-α [79]. In humans, stem-cell based therapy has been tried for stroke, with apparently good results, however different recent meta-analysis report that further investigation is needed to test clinical efficacy and safety [80,81].…”
Section: Antioxidant Treatmentmentioning
confidence: 99%
“…11 The qualities of included studies were defined as poor (score, 0e3), fair (score, 4e6), or good (score, 7e9). 12 Disagreements were resolved by discussions between the two reviewers or with another author.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Their intracerebral transplantation of NT2N cells has provided a model for current clinical trials in chronic stroke patients [39][40][41][42][43]. Additionally, studies have explored the peripheral transplantation of stem cells for acute stroke patients [40,42], which has paved the way for future clinical studies.…”
Section: Resultsmentioning
confidence: 99%